Causes of Failure and Repair Strategies for Flexible Pavements in Afghanistan - Zadran, Rahim Gul; Vasilievna, Braila Natalia (Stallion Journal for Multidisciplinary Associated Research Studies, 2026)
In this paper, a comprehensive review was made to explore the phenomenon flexible pavement failures within Afghanistan’s road network, which consists of 3,562 Km of regional highways, 9,754 km of Provincial roads and important rural roads. It seeks to categorize the main causes of pavement failures which stem from poor design choices and material selection, inadequate drainage systems and general lack of maintenance. Overloading with heavy vehicles further worsens roads leading to structural and functional failures which are marked by distress types such as edge and fatigue cracks, potholes, and rutting. The consequences of such pavement defects are serious and threaten the safety of transportation as well as the economy. With high rates of vehicle accidents, urban, and rural roads in shambles, there is profound need for effective repair and maintenance plans. It is recommended that measures of improvement such as Repairing Potholes with Asphalt Concrete (Plant Hot Mix AC) and Excel Patch (Cold Mix Asphalt), Crack Filling (1 Layer: 12mm Aggregate + CRS-2) and (2 Layers: 19mm + 12mm Aggregate + CRS-2), fog sealing, slurry sealing, Microsurfacing, and others that are suitable to Afghanistan’s weather and environment be incorporated. Also, a better pavement performance model should be suggested so as to achieve an optimal repair priority order to improve the endurance and safety of the road systems of Afghanistan.